Method for catalytically degrading polyester material by using ionic liquid and application

By using ionic liquid catalysts to catalytically degrade polyester materials under mild conditions, the problems of high energy consumption and complex processes in existing technologies have been solved, realizing an efficient and environmentally friendly method for polyester material recycling and simplifying the process flow.

CN121045642APending Publication Date: 2025-12-02CHANGHUA CHEMICAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202511181071.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-22
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

Existing technologies for polyester material recycling suffer from high energy consumption, environmental unfriendliness, and complex processes. In particular, the alcoholysis method often uses strong acid and strong base catalysts, leading to high-temperature reactions and complex post-processing.

Method used

Using ionic liquids as catalysts and glycols as alcoholysis agents, polyester materials are catalytically degraded under mild conditions. The anions in the ionic liquids attack the ester bonds, breaking the molecular chains and generating directly usable recycled polyether/ester polyols, avoiding the use of high temperatures and strong acids and alkalis.

Benefits of technology

It enables rapid degradation of polyester materials under mild conditions, with a high degradation rate, no need for post-treatment of the product, simplified process, reduced energy consumption, and environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005560776100000021
    Figure BDA0005560776100000021
  • Figure BDA0005560776100000031
    Figure BDA0005560776100000031
  • Figure BDA0005560776100000032
    Figure BDA0005560776100000032
Patent Text Reader

Abstract

The invention relates to a method for catalytically degrading a polyester material by using an ionic liquid and application of the polyester material, and mainly solves the technical problems of high energy consumption, environment unfriendliness and complex process in polyester material recovery research in the prior art. According to the technical scheme, the novel method for catalytically degrading the polyester material through the ionic liquid comprises the steps that the ionic liquid is used as a catalyst, diol is used as an alcoholysis agent, polyester is catalytically degraded, and the ionic liquid has the following general formula: A + B-(I); in the formula, A < + > is an organic alkali cation, and B <-> is an alkoxy anion, the problem is well solved, and the method can be applied to polyester recovery industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chemical degradation and recycling of polyester materials, and in particular to a method and application of catalytic degradation of polyester materials using ionic liquids. Background Technology

[0002] Polyurethane and PET polyester materials are widely used in packaging, construction, medical, aerospace, and home furnishing industries, and the amount of waste generated from them has been increasing rapidly in recent years. At the same time, substandard products produced during the manufacturing process also contribute significantly to the generation of waste materials. However, these polyester materials often possess a highly cross-linked three-dimensional network structure, flexible formulations, high hydrophobicity, and are difficult to dissolve or melt, increasing the difficulty of biodegradation and high-value recycling of these plastics.

[0003] The recycling methods for waste polyurethane and PET mainly include physical recycling, chemical recycling, energy recovery, mechanochemical recycling, and catalytic solvothermal recovery, with chemical methods being the most extensively studied. Polyester can gradually depolymerize into its original reactants under conditions of chemical reagents, catalysts, high temperature, and high pressure. Chemical recycling methods mainly include hydrolysis, alcoholysis, and ammonolysis. Among these, the mechanism of alcoholysis utilizes small-molecule alcohols, such as ethylene glycol, diethylene glycol, and triethylene glycol, as degrading agents to degrade and liquefy waste polyurethane foam and PET under certain reaction conditions. The alcoholysis recycling process is relatively simple, with a high liquefaction rate, and the resulting degradation products can be directly utilized. Existing research on alcoholysis recycling of polyurethane and PET polyester materials mostly uses metals or common industrial strong acid and base active centers as catalyst active centers, conducted at relatively high temperatures (180-200℃).

[0004] Chinese patent CN119143764 A discloses an ionic liquid catalyst for the chemical degradation of polyurethane, its preparation method, and its application. The ionic liquid synthesis uses a nitrogen-containing heterocyclic compound as a matrix, dissolving it in an organic solvent. The nitrogen heterocyclic compound is protonated under the influence of acids, and then separated and purified to form the ionic liquid catalyst. This catalyst is then used in the chemical degradation reaction of polyurethane at 150-200°C. However, the degradation products need to be allowed to stand and separate into layers; the upper layer is then used to obtain a mixed polyol of polyether and polyester types as a recycled product. In this invention, the ionic liquid is synthesized in a one-step process, with a catalytic dosage of only 0.5%-3%. The obtained product can be directly used for foaming without post-treatment. The process is simple, and the overall industrialization cost is controllable. Related methods generally suffer from high energy consumption, environmental unfriendliness, and complex processes due to difficulties in separating and purifying degradation products. Therefore, there is an urgent need for a highly industrialized method with mild reaction conditions, high degradation efficiency, and simple post-treatment to achieve the recycling, degradation, and high-value-added conversion of waste polyurethane. Summary of the Invention

[0005] One of the technical problems to be solved by this invention is that existing technologies for polyester material recycling research suffer from high energy consumption, environmental unfriendliness, and complex processes. This invention provides a method for the catalytic degradation of polyester materials using ionic liquids. This device has the advantages of achieving rapid degradation of polyester under mild conditions, not using ionic liquids that are environmentally unfriendly due to strong acids and alkalis, and having a simple process.

[0006] The second technical problem to be solved by the present invention is to provide a corresponding application of ionic liquid catalytic degradation of polyester materials to solve the first technical problem.

[0007] To solve one of the aforementioned technical problems, the present invention adopts the following technical solution: It includes using an ionic liquid as a catalyst and a glycol as an alcoholysis agent to catalyze the degradation of polyester materials; the ionic liquid includes the following general formula:

[0008] A + B - (I)

[0009] In the formula, A + B is an organic base cation. - It is an alkoxy anion.

[0010] In the above scheme, preferably, the A+ includes the following general chemical structural formula:

[0011]

[0012] In the formula, R1, R2, R3, R4, R5, and R6 are selected from one of H, C1-C8 alkyl, alkoxy, cycloalkyl, alkenyl, phenyl, and benzyl.

[0013] B - The general chemical structural formula is:

[0014] RO -

[0015] In the formula, R is selected from alkyl C1 to C8.

[0016] In the above scheme, preferably, the method for preparing the ionic liquid is as follows:

[0017] The reagent is prepared by adding an alkoxy donor to an organic base dropwise under an inert gas atmosphere and an ice bath. After the addition is complete, the mixture is stirred at room temperature to obtain the final product.

[0018] In the above scheme, preferably, the organic base is selected from at least one of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5,7-triazabicyclo[4.4.0]decen-5-ene (TBD), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), or an organic guanidine; the alkoxy donor reagent is selected from at least one of methanol, ethanol, and n-propanol.

[0019] In the above scheme, preferably, the diol is selected from at least one of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol or butanediol.

[0020] In the above scheme, preferably, the mass ratio of the ionic liquid catalyst to the total mass of the polyester material and alcoholysis agent is 0.5:~3:100.

[0021] In the above scheme, preferably, the reaction temperature is 100-140℃, the reaction time is 4-8h, and the reaction pressure is atmospheric pressure or slightly positive pressure.

[0022] In the above scheme, preferably, the polyester material is polyurethane semi-rigid foam or recycled PET bottle flakes.

[0023] To solve the second technical problem mentioned above, the present invention adopts the following technical solution: the application of a method for catalytic degradation of polyester materials using ionic liquids in polyurethane semi-rigid or rigid foams.

[0024] After the expected degradation time is reached, the polyester degradation rate and the yield of recycled polyether / ester polyol are calculated according to the following formula.

[0025]

[0026] In the formula, Y is the mass of polyester feed and X is the mass of undegraded polyester.

[0027] This invention provides a method for the catalytic degradation and recovery of polyester materials using ionic liquids. Due to the unique anionic and cationic structure and high reactivity of ionic liquids, the ester bonds (-COO-) in the polyester molecular chain are broken through nucleophilic substitution reactions. The RO- anion in the ionic liquid attacks the carbonyl carbon of the ester bond, forming a tetrahedral intermediate. The intermediate decomposes, leading to the breakage of the ester bond and the generation of carboxylic acid and alcohol terminals. Under alkaline conditions, the carboxylic acid further transforms into carboxylate salts (such as R-COO-), shifting the reaction equilibrium to the right. This invention uses ionic liquids to replace conventional strong acid and strong base recovery methods, avoiding the energy consumption problems associated with high-temperature reactions, making it environmentally friendly. Furthermore, the ionic liquid does not contain potassium or sodium elements, eliminating the need for post-treatment with potassium or sodium ions, and simplifying the process. Rapid degradation of polyester is achieved under mild conditions and with low catalyst dosage, demonstrating good technical performance. Attached Figure Description

[0028] Figure 1 The infrared spectrum of the ionic liquid [DBUH][CH3O] is shown below.

[0029] Figure 2 The infrared spectrum of the ionic liquid [TBDH][BNO] is shown.

[0030] Figure 3 Images of polyurethane semi-rigid foaming of recycled polyether polyols;

[0031] Figure 4 Images of polyurethane rigid foaming using recycled polyester polyols. Detailed Implementation

[0032] The technical solution of the present invention will be further described below through specific embodiments and in conjunction with the accompanying drawings.

[0033] Table 1. List of raw materials for catalyst synthesis and alcoholysis agent:

[0034]

[0035] Table 2 List of foaming raw materials:

[0036]

[0037] Example 1

[0038] This embodiment provides ionic liquids based on monool groups as anions and their preparation methods. Specifically, different basic ionic liquids are prepared by adding monools dropwise to strong organic bases under nitrogen atmosphere in an ice bath, and then stirring uniformly at room temperature.

[0039] Taking the preparation of 1,8-diazabicyclo[5.4.0]undec-7-ene-methanol ([DBUH][CH3O]) as an example: 7.61 g (0.05 mol) of 1,8-diazabicyclo[5.4.0]undec-7-ene was weighed and placed in a three-necked flask. 1.60 g (0.05 mol) of methanol was weighed and added dropwise to the 1,8-diazabicyclo[5.4.0]undec-7-ene under an ice bath. After the addition was complete, the mixture was cooled to room temperature and reacted for 24 hours under a N2 atmosphere. A clear and transparent liquid ionic liquid catalyst product was obtained. (See the infrared image below.) Figure 1 The infrared spectrum of Example 3 is shown below. Figure 2 .

[0040] Examples 2-8

[0041] Other ionic liquids involved in this invention can be obtained by changing suitable raw materials and using a preparation method similar to that in Example 1. Table 3 shows the mass (g) of each component raw material.

[0042] Table 3 Ionic liquid raw material components in Examples 2-8

[0043]

[0044]

[0045] Example 9

[0046] This embodiment provides a method for preparing polyether polyols and foaming them by catalytic degradation of polyurethane using ionic liquids, as detailed below:

[0047] The ionic liquid 1,8-diazabicyclo[5.4.0]undec-7-ene-methanol ([DBUH][CH3O]) (catalyst, 0.5 g), diethylene glycol (alcohololysis agent, 50 g), and semi-rigid polyurethane foam (powder, 50 g) prepared in Example 1 were sequentially added to a three-necked flask and sealed. Under a N2 atmosphere, the reaction temperature was controlled at 130°C, and the depolymerization reaction continued for about 4 hours after the foam liquefied. After the reaction was completed, the material was filtered while hot to remove trace amounts of non-degradable components, and the liquid product was collected to obtain recycled polyether. The degradation rate of the polyurethane semi-rigid foam was calculated to be 99.9%, and the recycled polyester yield was 99.9%. Further analysis of relevant indicators showed an acid value of 1.31 mg KOH / g, a hydroxyl value of 550.6 mg KOH / g, and a viscosity of 6440 mPa·s. The recovered polyether polyol was used for re-foaming, as shown in the appendix. Figure 3 .

[0048] (1) Preparation of component A: 118.5g

[0049] Weigh out the following polyether polyols: 46g of CHE-2801L, 35g of CHE-303, 10g of CHE-210, 15g of recycled polyether, 106g of diethylene glycol, 0.25g of PC-37 catalyst, 4.8g of water, 1g of antioxidant 1135, and silicone oils: 0.2g of AK-8805 and 0.25g of AK-158. Add them to the reactor and stir at room temperature for 1.5 hours to mix thoroughly.

[0050] (2) Weigh component B: 100g; Component B is specifically M20S;

[0051] (3) Component A and component B are mixed evenly by a high-pressure sprayer at a mass ratio of 1.185:1, atomized and foamed, and the foam is rapidly formed and cured to obtain semi-rigid foam. Its mechanical properties are shown in Table 4.

[0052] Table 4 Results of mechanical properties of Example 9

[0053]

[0054]

[0055] Examples 10-14

[0056] Each step in Examples 10-14 was performed according to Example 9. The mass of the degraded polyurethane foam was 50g, the mass of the alcoholysis agent was 50g, and the degradation time was 4 hours. The differences were in the type and amount of catalyst (g), the type of alcoholysis agent, the degradation temperature (°C), and the properties of the resulting recycled polyether polyol and the recycled foam.

[0057] Table 5. Degradation components and performance indicators of re-foaming after degradation in Examples 10-14

[0058]

[0059] Example 15

[0060] This embodiment provides a method for catalytic degradation of recycled PET bottle flakes using ionic liquids, as detailed below:

[0061] The ionic liquid 1,8-diazabicyclo[5.4.0]undec-7-ene-methanol ([DBUH][CH3O]) (catalyst, 3g), diethylene glycol (alcohololysis agent, 50g), and PET bottle flakes (flakes, 50g) prepared in Example 1 were sequentially added to a reaction flask and sealed. The reaction temperature was controlled at 130℃ under normal pressure, and the depolymerization reaction was carried out for approximately 4 hours. After the reaction, the material was filtered while hot to remove trace amounts of non-degradable components. The collected liquid product yielded recycled polyether. Calculations showed that the PET bottle flake hydrolysis rate was 99.9%, and the recycled polyester yield was 99.9%. Further analysis of relevant indicators revealed an acid value of 10.16 mg KOH / g, a hydroxyl value of 437 mg KOH / g, and a viscosity of 4230 mPa·s. The recovered polyester polyol was used for re-foaming (see attached...). Figure 3 ).

[0062] The foaming formula is as follows: Preparation component A: 100g

[0063] (1) Weigh the following respectively: polyether polyols: NJ-8238, 14.1g; SKR-240B, 12.1g; PS-3152, 15.35g; recycled polyester, 20g; flame retardant: TCPP, 19.7g; catalyst: a mixed catalyst composed of 0.1g N,N-dimethylcyclohexylamine, 0.61g potassium isooctanoate, and 0.42g 2-hydroxy-N,N,N-trimethyl-1-propylamine carbamate; physical foaming agent: HFC245fa, 11g; chemical foaming agent: water, 2.45g; additives: lactic acid, 0.17g.

[0064] (2) Add the weighed polyether polyol, flame retardant, catalyst, physical foaming agent, chemical foaming agent and additives into the reactor and stir at room temperature for 1.5 hours to mix thoroughly.

[0065] (3) Weigh component B: 120g; Component B is specifically PM-200;

[0066] (4) Component A and component B are mixed uniformly in a mass ratio of 1:1.2 using a high-pressure sprayer, atomized and foamed, and the foam is rapidly formed and cured to obtain rigid foam. Its mechanical properties are shown in Table 1. Its mechanical properties are shown in Table 6.

[0067] Table 6 Results of mechanical properties of Example 15

[0068] Test metrics numerical values Compressive strength (N) 185 <![CDATA[Density (kg / m 3 )]]> 31.2 Closed-cell ratio (%) 97.8 Dimensional stability (-20℃ to 80℃ cycling for 48 hours) (%) 1.17 Water absorption rate (%) 0.82 Thermal conductivity (W / m·K) 0.023167

[0069] Examples 16-20

[0070] Each step in Examples 16-20 was performed according to Example 15. The mass of the PET bottle flakes degraded was 50g, the mass of the alcoholysis agent was 50g, and the degradation time was 4 hours. The differences were the type and amount of catalyst (g), the type of alcoholysis agent, the degradation temperature (°C), and the indicators of the resulting recycled polyether polyol and the recycled foam performance indicators.

[0071] Table 7 Degradation components and performance indicators of re-foaming after degradation in Examples 16-20

[0072]

[0073]

[0074] Comparative Example 1:

[0075] Patent CN107955206A discloses a method for degrading and recycling polyether polyols from waste polyurethane foam. In a 2L high-pressure reactor equipped with a stirrer, heating and temperature control device, cooling device, and pressure sensor, 600g of alcoholysis solution is added, wherein the mass ratio of ethylene glycol to propylene glycol in the small molecule alcohol is 3:2. The mixture is heated to 150℃, and then 8g of a degradation aid is added, wherein the mass ratio of triethanolamine to potassium hydroxide in the degradation aid is 3:2. Then, 800g of pulverized waste refrigerator polyurethane foam (density 40Kg / m³) is gradually added. 3 The mixture was added to a reaction vessel and reacted at 160℃ for 5 hours to obtain a crude polyether polyol mixture. Then, the mixture was heated to 150℃ and degassed under negative pressure for 1 hour to obtain the recovered crude polyether polyol. The recovered polyether polyol has the following properties: hydroxyl number: 580 mg KOH / g; amine value: 90 mg KOH / g; viscosity at 25℃: 5400 mPas; appearance: wine-red transparent liquid.

[0076] Comparative Example 2:

[0077] Patent CN119143764A discloses an ionic liquid catalyst for the chemical degradation reaction of polyurethane, its preparation method, and its application. In a 5L reactor equipped with mechanical stirring, heating and temperature control, and pressurization devices, 500g of acidolytic agent and 5g of synthesized ionic liquid catalyst are added in a mass ratio of 100:1, and the mixture is heated to 200℃. The acidolytic agent consists of succinic acid and adipic acid in a mass ratio of 3:1, and the ionic liquid catalyst is [TBDH][Pyrazole]. The acidolytic agent and catalyst are preheated, and then 2kg of pulverized rigid polyurethane foam powder is added in a single feeding operation, with the ratio of rigid polyurethane foam powder to acidolytic agent being 4:1. After 1 hour of reaction, the rigid polyurethane foam powder completely disappeared. After 3 hours of reaction, the basic physical properties of the degradation products showed no significant change: acid value of 0.2 mg KOH / g, hydroxyl value of 185 mg KOH / g, amine value of 0.2 mg KOH / g, viscosity of 5000 mPa·s, water content of 0.03%, and color of black. After standing and stratification, the upper layer was taken as the recovered polyether-polyester mixed polyol, and the lower layer was the degraded polyamide compound, with a ratio of 4:6. Re-foaming was performed using the recovered polyether-polyester mixed polyol. When the recovered polyether-polyester mixed polyol replaced 20 wt% of the original polyol, the mechanical properties of the recycled polyurethane foam still met the performance indicators of commercial polyurethane foam.

[0078] Compared with Comparative Example 1, the catalyst dosage in this embodiment of the invention can be as low as 0.5%, the catalytic reaction temperature is only 100-140℃, and there is no metal residue, so no refining post-treatment is required and it can be directly used for foaming; compared with Comparative Example 2, the catalytic reaction temperature in this invention is only 100-140℃, which is far below 200℃, effectively saving energy consumption. The product obtained is a homogeneous transparent liquid product, and no stratification phenomenon occurs. No post-treatment is required and it can be directly applied to foaming.

Claims

1. A method for catalytic degradation of polyester materials using ionic liquids, comprising using an ionic liquid as a catalyst and a glycol as an alcoholysis agent to catalytically degrade the polyester materials; wherein the ionic liquid comprises the following general formula: A + B - (Ⅰ) In the formula, A + B is an organic base cation. - It is an alkoxy anion.

2. The method for catalytic degradation of polyester materials using ionic liquids according to claim 1, characterized in that, The A+ mentioned includes the following general chemical structural formulas: In the formula, R1, R2, R3, R4, R5, R6, and R7 are each selected from H, C1-C8 alkyl, alkoxy, cycloalkyl, alkenyl, phenyl, and benzyl. B - The general chemical structural formula is: R-O - (Ⅵ) In the formula, R is selected from alkyl C1 to C8.

3. The method for catalytic degradation of polyester materials using ionic liquids according to claim 1, characterized in that, The method for preparing the ionic liquid is as follows: The reagent is prepared by adding an alkoxy donor to an organic base dropwise under an inert gas atmosphere and an ice bath. After the addition is complete, the mixture is stirred at room temperature to obtain the final product.

4. The method for catalytic degradation of polyester materials using ionic liquids according to claim 3, characterized in that, The organic base is selected from at least one of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 1,5,7-triazabicyclo[4.4.0]decen-5-ene (TBD), 1,5-diazabicyclo[4.3.0]nonene-5 (DBN), or an organic guanidine; the alkoxy donor is selected from at least one of methanol, ethanol, and n-propanol.

5. The method for catalytic degradation of polyester materials using ionic liquids according to claim 1, characterized in that, The diol is selected from at least one of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, or butanediol.

6. The method for catalytic degradation of polyester materials using ionic liquids according to claim 1, characterized in that, The mass ratio of the ionic liquid catalyst to the total amount of polyester material and alcoholysis agent is 0.5 to 3:

100.

7. The method for catalytic degradation of polyester materials using ionic liquids according to claim 1, characterized in that, The reaction temperature is 100–140°C, the reaction time is 4–8 h, and the reaction pressure is atmospheric pressure or slightly positive pressure.

8. The method for catalytic degradation of polyester materials using ionic liquids according to claim 1, characterized in that, The polyester material is polyurethane semi-rigid foam or recycled PET bottle flakes.

9. The application of the method for catalyzing polyester materials using ionic liquids as described in claim 1 in polyurethane semi-rigid or rigid foams.

Citation Information

Patent Citations

  • Method for degrading waste polyurethane foam to recycle polyether polyol

    CN107955206A

  • Ionic liquid type catalyst for catalyzing chemical degradation reaction of polyurethane as well as preparation method and application of ionic liquid type catalyst

    CN119143764A

Cited By

  • Flame-retardant disassembling agent of polyurethane adhesive and lossless disassembling method of power battery pack

    CN121885831A

  • A method and system for recovering glycolic acid

    CN122608504A